(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the availability of teaching performance for middle school mathematics teachers according to information technology in the classroom, and the research sample consisted of (60) female teachers. One of the mathematics teachers who study in the intermediate day schools of the Directorate of Education of Baghdad Governorate, Al-Karkh II, and the researcher used a tool to achieve this purpose, which was represented by the observation card and presented to a group of arbitrators, and its psychometric properties were extracted. The researcher used a set of statistical methods, including the t-test for one sample, Pearson correlation coefficient, weighted average, and hypothetical average, and the results showed a weakness in the level of teaching performance of the teachers of the research sample by teaching according to information technology, and the research came out with a set of recommendations and suggestions